Particle Size Optimization of Melinjo (Gnetum gnemon L.) Seed Hardshell: A Potential Antioxidant Alternative - Marlina Indriastuti; I Ketut Adnyana; Rika Hartati; Heni Rachmawati (Journal of Mathematical and Fundamental Sciences, 2024)
Natural ingredients can have extraordinary potential as alternative medicines due to their accessibility and cost-effectiveness. Application of these ingredients should consider solubility and permeability, which determine the success of pharmaceutical characteristics formulation and biological activity indication. In this context, physical manipulation, specifically particle size reduction, is an effective strategy to address these issues. Previous research has explored active compounds in the stilbenoid group, found in the outer skin, hard shell, and endosperm of melinjo (Gnetum gnemon L.) seeds, functioning as antioxidant. Based on the potential as antioxidant, stilbenoid compounds, including resveratrol, contained in melinjo seed hardshell have shown significant pharmacological effects. Therefore, this research aimed to investigate the potential of melinjo seed hardshell extract as a natural antioxidant alternative by modifying the particle size through a grinding process to obtain nanoparticles. The analysis was carried out using ball milling to enhance the solubility of melinjo seed hardshell extract by increasing the saturated solubility and surface area of the particles. The results showed that the total phenol content and the antioxidant power increased significantly (p < 0.05) after ball milling. Melinjo seed hardshell nanoextract is reported herein as a promising source of natural antioxidant from local Indonesian plants.